Thermal Radiation Modelling in Tunnel Fires (Advances in Applied Mathematics and Mechanics, 2021)
Modelling based on Computational Fluid Dynamics (CFD) is by noweffectively used in fire research and hazard analysis. Dependingon the scenario, radiative heat transfer can play a very importantrole in enclosure combustion events such as tunnel fires. In this work,the importance of radiation and the effect of the use of different approachesto account for it were assessed. Firstly, small-scale tunnel fire simulationswere performed and the results compared with experimental data, then realisticfull-scale scenarios were simulated. The results show up the capability of CFDmodelling to reproduce with good approximation tunnel fires. Radiation proved tobe noteworthy mainly when the scale of the fire is relatively large. Among thevarious approaches employed to simulate radiation, the use of the Discrete Transfermodel gave the most accurate results, mainly when the absorption-emission characteristicsof the combustion products were taken into account. Finally, the suitability of theuse of CFD in quantitative Fire Hazard Analysis is discussed.